Price transmission and benefit analysis of producers in the cavendish banana industry - Genise, Jessamyn O.,&eauthor.; Digal, Larry N. (2009)
The study attempted to identify the best linkage of small-scale producers to high value export market in the Cavendish banana industry. Producer linkages are in the form of different contractual arrangements that tie up both producers and exporters to take part in the production. Initially, industry trends analysis was presented to provide background of the Cavendish banana industry. In determining the best linkage, net and gross income comparisons were done across different contractual arrangements of producers among selected four exporters. Assessment on the advantages and disadvantages of the different contractual arrangements was also employed to validate the quantitative measure of benefits. For producers in the growership scheme, success-failure factors were evaluated to determine recommended attributes in gaining benefits. To examine the overall competitiveness of producers in the chain, price transmission elasticity was the method used. Results showed that growership type of contract provides the greatest benefit to landowners. Producers in the Philippines also have relatively small influence on the retail price of exported banana in the Japan market. Among the exporters included in the study, growers of Company C received the largest income computed per box of banana. For small-scale producers organizing into a cooperative gives them the advantage. Furthermore, independence of the cooperative from the buying exporter is much desired because of high bargaining power perceived. Access to capita and the production capacity are important factors for cooperatives to maintain a high degree of bargaining power. Efficiency in the production operations is realized through Individual Farming System. Interventions of NGOs and Gos play a significant role. Small-scale producers need assistance in various forms, financial, legal, and infrastructures.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao
Keywords: Cavandish banana